Noise in MgO barrier magnetic tunnel junctions with CoFeB electrodes; influence of annealing temperature - FENG, GEN; COEY, JOHN MICHAEL DAVID (American Institute of Physics, 2007)
Low frequency noise has been measured in magnetic tunnel junctions with MgO barriers and magnetoresistance values up to 235%. The authors investigated the noise for different degrees of crystallization and CoFeB/MgO interface quality depending on the annealing temperature. The authors report an extremely low 1/ f noise, compared to magnetic junctions with Al2O3 barriers. The origin of the low frequency noise is discussed and it is attributed to localized charge traps with the MgO barriers.
PUBLISHED
Keywords: Physics